ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PT SILOAM INTERNATIONAL HOSPITALS TBK SEBELUM DAN SESUDAH ADANYA PANDEMI COVID-19 - Annisa Alifa Ramadhani; Desyria Pratiwi (Institut Bisnis Muhammadiyah Bekasi, 2023)
Financial performance is an analysis carried out to find out how far the company is progressing through the application of correct and correct financial implementation principles. The performance of a company is a description of the company's financial condition which is analyzed using financial analysis tools to determine whether the company's financial condition is good or bad which reflects the performance of a certain period. The purpose of this study is to analyze the comparison of the company's performance of PT Siloam International Hospitals Tbk before and after the Covid-19 pandemic, financial report data obtained from the Indonesia Stock Exchange for the 2018-2021 period. Analysis of financial performance is seen from the company's financial ratios, the financial ratios analyzed are liquidity ratios, solvency ratios, and profitability ratios and can be assessed or analyzed better before or after the Covid-19 pandemic based on the industry average of each ratio.